PROBIOTIC CORRECTION OF ANTIBIOTIC ASSOCIATED INTESTINAL DYSBACTERIOSIS IN CHILDREN - S.V. Bel'mer; N.E. Shchigoleva; A.I. Khavkin; A.V. Gorelov; S.F. Blat ("Paediatrician" Publishers LLC, 2007)
An open comparative randomized study evaluates the probiotic therapy efficacy in 59 children aged 6-17 with a medication containing freeze dried strains of bifidobacterium infantis V. liberorum, lactobacillus acidophilus and streptococcus faecium (Linex, Lek, Slovenia). The treated disease was antibioticassociated intestinal dysbacteriosis developed on the back ground of antichelicobacterial therapy. The major group comprised 38 patients, and the comparison group comprised 21 children. Patients from both groups were comparable in terms of demographic and clinical characteristics. The study focused on the clinical data and the results of the intestinal flora and volatile fatty acid survey. The study showed that in the majority of patients antichelicobacterial therapy concurs with antibiotic-associated intestinal dysbacteriosis. Yet, the medication containing freeze dried strains of bifidobacterium infantis V. liberorum, lactobacillus acidophilus and streptococcus faecium reduces the antibiotic-associated intestinal dysbacteriosis development risk, and its effect manifests itself through clinical improvement, normalized intestinal micro flora and restored metabolism. Key words: antibiotic-associated dysbacteriosis, children, probiotics, treatment, prevention.